Dana Desa Untuk Pembangunan Infrastruktur Nagari Dan Implikasinya Terhadap Partisipasi Masyarakat Di Nagari Bisati Kecamatan VII Koto Sungai Sariak Kabupaten Padang Pariaman - Dwi Hastuti; Asdi Agustar; Ifdal (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2024)
This study aims to determine the process of utilizing village funds, the type and amount of infrastructure built and the amount of funds used for infrastructure development and to find out the implications of having village funds for infrastructure development on community participation in Nagari Bisati, sub-district VII Koto, Padang Pariaman Regency. This research uses the case study method because this research aims to understand the object it is researching, in this case community participation in the village of Bisati in building village infrastructure, especially roads, bridges and irrigation after village funds can be used to build the infrastructure. The procedure for obtaining qualitative research data, from case studies obtained from interviews, observations and archives. Data collection will be carried out using 2 (two) methods/techniques, namely to obtain primary data, in-depth interviews will be carried out with key informants. To obtain secondary data, documentation techniques will be used. From the results of research that has been carried out, the management and utilization of village funds in Nagari Bisati has been carried out well, starting from planning to accountability as measured by the principles of transparency, accountability, participation as well as order and discipline to give good results and values. The planning process, which begins with rembuk korong, is a way to pick up people's aspirations from the bottom up, which is one of the keys for successful development. Because the community itself knows their needs, problems and abilities. The implications of using Village Funds for community participation in Nagari Bisati are very good. With village funds, the community is more motivated to develop. This can be seen by the large number of people who donate their land without being paid, labor, materials, food and drink, and money. People overseas send money to purchase materials. The term